The Hellenistic Far East in Historical Fiction. Ancient History, Modern Ideologies - Rachel Mairs (Studia Hercynia, 2021)
It has become a truism that it is impossible to reconstruct a narrative history of Central Asia in the period after Alexander. Scant literary or epigraphic sources, and the pitfalls of reconstructing dynastic histories from coins, make scholars wary of writing ‘history’ in the traditional academic sense. It may therefore come as a surprise that Hellenistic-period Central Asia has emerged as the setting for a number of historical novels. This paper aims to deconstruct the research process that lies behind the crafting of narrative in several such pieces. It will identify the primary sources and works of scholarship used by authors, and explore how these have been used to construct visions of Hellenistic Central Asia which reflect not just on the ancient record, but on the modern authors’ political and social context. The works discussed will include Rudyard Kipling’s The Man Who Would Be King (on Alexander and his routes in Afghanistan), Teodor Parnicki’s (1955) Koniec Zgody Narodów/The End of the Concord of Nations (which explores the resonances of cultural encounter in Hellenistic Central Asia for the post-War world), and Gillian Bradshaw’s (1990) Horses of Heaven (which uses a hypothetical Graeco-Bactrian alliance with Ferghana as the backdrop for historical romance).